New European Security Strategy: The transatlantic factor - Annegret Bendiek; Markus Kaim (Stiftung Wissenschaft und Politik (SWP), 2015)
A wave of new foreign policy and security challenges have made certain aspects of earlier European Union strategic thinking obsolete. In response, Federica Mogherini, the High Representative of the European Union for Foreign Affairs and Security Policy, has announced her intention to prepare a new European Security Strategy (ESS). The process is to proceed in two stages. First, an analysis of the current strategic coordinates within which the EU's foreign and security policy must operate will be presented to the summit of heads of state and government in Brussels in June 2015. The second stage will comprise an inclusive, pan-European debate on the EU's external and security roles. The results of that discussion will flow into a new European Security Strategy, whose publication is due in 2016. The question for the member states today is what kind of role the EU should play in the world, and in particular what its relationship to the United States should look like. (SWP Comments)
Keywords: 320